السلوكية الوراثية لبعض صفات الغلة في التبغ الشرقي (Nicotiana tabacum) - جابر بدر; المهر نجوى (Latakia University Journal -Biological Sciences Series, 2018)
تم دراسة ظاهرة قوة الهجين والمقدرتين العامة والخاصة على الخلط على خمس صفات من مكونات الغلة في التبغ الشرقي (Nicotiana tabacum L. )، حيث تم استخدام سبعة أصناف وهجنها نصف التبادلية (21هجينا)، وتمت الزراعة في ثلاثة مواقع في اللاذقية. بينت دراسة تقييم الآباء وجود تباينات في جميع الصفات بين الأنماط الوراثية الأبوية المستخدمة في هذه الدراسة. ولقد لوحظت قوة هجين ايجابية عالية الدلالة الإحصائية لجميع الصفات في بعض الهجن، ولكنها اختلفت في مقدارها. فلقد أظهر الهجينان بصما x جب حسن وبصما x شمباتي ظاهرة قوة هجين لجميع الصفات المدروسة، وقد يعود ذلك إلى التباين الوراثي بين الآباء. ومع ذلك، أبدت معظم الهجن سيادة جزئية، وربما يعود ذلك إلى الفعل التراكمي للمورثات. ولقد كانت تقديرات تباين المقدرة العامة على الخلط ذات دلالة إحصائية لجميع الصفات المدروسة، بينما كانت تقديرات تباين المقدرة الخاصة على الخلط ذات دلالة إحصائية لجميع الصفات المدروسة ماعدا صفة عرض الورقة. وكانت تباينات المقدرة العامة على الخلط أعلى من تباينات المقدرة الخاصة على الخلط بالنسبة لجميع الصفات المدروسة، مشيرة إلى هيمنة الفعل التراكمي للمورثات. ولقد تميز الصنف شمباتي بمقدرة عامة عالية على الخلط بالنسبة لجميع الصفات المدروسة، بينما أبدت الأصناف الأبوية الأخرى قيما مختلفة للمقدرة العامة على الخلط وفقا للصفات المختلفة. وتوحي النتائج التي تم الحصول عليها من هذا العمل، أن الآباء ذات المقدرة العامة العالية على الخلط لصفة ما، تعطي عند تهجينها هجنا ذات مقدرة خاصة على الخلط عالية للصفة نفسها. ويمكن لهذه المقدرة الخاصة على الخلط أن تتمتع بالديمومة عبر الأجيال، لأنها ناتجة عن التفاعل من النمط (مورثات ذات أثر تراكمي x مورثات ذات أثر تراكمي). ويمكن الاعتماد على هذه الحقيقة في ممارسة الانتخاب بكفاءة عالية. The effect of heterosis and combining ability estimates was studied in oriental tobacco (Nicotiana tabacum L.) for five yield component characters, using 7x7 half diallel cross ie 21 hybrids, in three locations in lattakia zone. Parent evaluation demonstrates the existence of variabilities for all characters between all Parental genotypes used in this study. Highly significant positive heterosis was observed for all the characters in some hybrids, but they varied in the magnitude of heterosis. So, the two hybrids Basma x Jep Hassan and Basma x Champati manifested heterosis for all traits studied ,This is perhaps due to the genetic diversity between parents. However, most hybrids manifested partial dominance, perhaps due to the additive gene action. Estimates of general combining ability (GCA) variance were significant for all the characters studied, whereas specific combining ability (SCA) variance was significant for all characters except for leaf width. The GCA variances were higher than that of SCA for all the characters studied indicating the predominance of additive gene action. Champati, characterized by high GCA for all characters studied, whereas the other parental varieties presented different GCA values according to the different traits. Results obtained from this work suggest that parents with high GCA for one trait, when crossed, give hybrids with high SCA for the same trait. This SCA may be durable during the generations, because it is the result of interaction between (additive genes x additive genes). So, this fact may be useful in selection practice with high performance.